2013
DOI: 10.1186/2193-1801-2-534
|View full text |Cite
|
Sign up to set email alerts
|

Commercial versus synthesized polymers for soil erosion control and growth of Chinese cabbage

Abstract: Soil erosion leads to environmental degradation and reduces soil productivity. The use of anionic polyacrylamide (PAM) and synthesized biopolymer (BP) using lignin, corn starch, acrylamide, and acrylic acid were tested to evaluate soil erosion, water quality, and growth of Chinese cabbage (Brassica campestris L.). Each treatment of PAM and BP was applied at 200 kg ha-1 to loamy sand soil and subjected to a slope of 36% with a 20 mm h-1 simulated rainfall. Application of BP decreased soil pH compared to the unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…They also indicated that these SH are potential candidates to be applied as an alternative to combat of global climate change because they can improve the soil properties, mainly in conditions of reduced moisture availability. Other authors investigated the applicability of the polymers, common hydrogels and SH as strategies to improve the soil properties [184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201].…”
Section: Application As Soil Conditionersmentioning
confidence: 99%
“…They also indicated that these SH are potential candidates to be applied as an alternative to combat of global climate change because they can improve the soil properties, mainly in conditions of reduced moisture availability. Other authors investigated the applicability of the polymers, common hydrogels and SH as strategies to improve the soil properties [184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201].…”
Section: Application As Soil Conditionersmentioning
confidence: 99%
“…It is important to note that soil and water conservation are strongly linked (Wang et al 2015). Soil erosion is a natural process resulting primarily from water and wind action (Lee et al 2013) and is highly dependent on soil water content (Ramos and Mart ınez-Casasnovas 2007). Therefore, to achieve sustainable food production and to reduce soil loss through erosion, different agricultural practices have been adopted in arid and semi-arid regions to increase soil water holding capacity (Chen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular case of olive orchards, this effect is even greater, because adventitious flora is frequently removed through tillage in order to reduce the competition for water with the olive tree (Espejo‐Pérez, Rodríguez‐Lizana, Ordóñez, & Giráldez, ). This practice increases the soil erosion risk (Fernández‐Romero, Parras‐Alcántara, Lozano‐García, Clark, & Collins, ; Lee, Chang, Chang, & Ok, ), because it leaves it unprotected against heavy rains (Pastor, ). The result is a strong hydraulic erosion, which produces substantial soil loss in olive orchards (Cerdà, Lavee, Romero‐Díaz, Hooke, & Montanarella, ; Gómez et al, ), getting over 400 Mg ha −1 in some extreme downpours (Vanwalleghem & Giráldez, ).…”
Section: Introductionmentioning
confidence: 99%